THE INFLUENCE OF BRAND AMBASSADOR AND BRAND IMAGE ON PURCHASE DECISIONS FOR L'ORÉAL PARIS PRODUCTS IN MEDAN CITY - Situmorang, Putri Abigel; Adlina, Hafiza; Siregar, Onan Marakali (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2022)
The appearance of Covid-19 altered almost everyone's way of life. The shift from physical to internet buying exemplifies lifestyle changes that are evident. In addition, the Covid-19 has led to an upsurge in consumption. The cosmetics business is likewise affected by the shift from offline to online purchasing habits. L'Oréal Paris is one of the cosmetic brands available in Indonesia. This research intends to examine the impact of brand ambassadors and brand image on L'Oréal Paris product purchase choices in the city of Medan. This study used quantitative research using an associative methodology. Sampling was conducted using the approach of purposive sampling, with 100 respondents serving as samples. This study's main data was collected via the distribution of Google Forms surveys, while secondary data was gained through a review of the relevant literature. The data analysis method consists of the validity test, the reliability test, the classical assumption test, multiple linear regression analysis, and the hypothesis test. According to the study's results, both the brand ambassador and brand image have a significant influence on customer purchasing decisions. Brand ambassador and brand image are elements that impact buying decisions simultaneously.